Ethics and performance: Understanding the psychological contract of the taxation from the view of the employee tax - Indrawati Yuhertiana; Hero Priono; Rina Moestika Setyaningrum; Sri Hastuti (Universitas Hayam Wuruk Perbanas, 2015)
There is a phenomenon related to the dysfunctional behavior of unscrupulous tax officials and the reluctant of taxpayers to pay the tax. This study aims to explore the evidence of psychological tax contract in a tax official perspective. It proposes modeling the effect of Indonesia tax reform process for determining the ethics as the important variable that affects the tax officials’ performance. It also examines the effect of organizational commitment, culture, and tax reform on tax ethics. There were 128 tax officials working in three cities of East Java that were selected as the respondents. The questionnaires were distributed directly to the respondents. Partial Least Square was used to test the hypotheses. It was found that organizational commitment, organizational culture, and tax reform have a direct contribution to tax official ethics. However, understanding the ethics of taxation was not proved to be the moderating variable for the relationship between the organizational commitment and organizational change and the policies of rotation system explain why ethics failed as moderating variable.